2014
DOI: 10.1002/2013gc005182
|View full text |Cite
|
Sign up to set email alerts
|

Off-fault long-term damage: A condition to account for generic, triangular earthquake slip profiles

Abstract: Natural earthquake slip profiles have a generic triangular shape which the available rupture dynamics models fail to reproduce. Long-term faults are embedded in long-damaged crustal material, and the properties of the long-term damage vary both across and along the faults. We examine the effects of the predamaged state of the medium on the earthquake slip distributions. We simulate long-term damage by the decrease in the elastic modulus of the medium around the fault. We model the dynamic crack-like rupture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 120 publications
(331 reference statements)
5
81
1
Order By: Relevance
“…We highlight six examples of displacement profiles measured on Afar and Asal‐Ghoubbet faults with different location, length, and maximum cumulative displacement (Figure ). Most profiles have a fairly triangular and asymmetric envelope shape, consistent with the generic shape of displacement‐length distribution observed on both long‐term faults [e.g., Manighetti et al ., , 2009; Scholz , ; Soliva and Benedicto , ; Nicol et al ., ; Martel and Shacat , for normal faults; e.g., Peacock , ; Bürgmann et al ., ; McGrath and Davison , ; Pachell and Evans , ; Farbod et al ., for strike‐slip faults; e.g., Ellis and Dunlap , ; Shaw et al ., ; Davis et al ., for reverse faults] and individual earthquake ruptures [e.g., Scholz and Lawler , ; Manighetti et al ., ; Wesnousky , ; Perrin et al ., ; Cappa et al ., ]. On each fault, the distribution of cumulative displacement along‐strike appears as a fluctuating signal, dominated by large peaks separated by narrower troughs (Figure a).…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…We highlight six examples of displacement profiles measured on Afar and Asal‐Ghoubbet faults with different location, length, and maximum cumulative displacement (Figure ). Most profiles have a fairly triangular and asymmetric envelope shape, consistent with the generic shape of displacement‐length distribution observed on both long‐term faults [e.g., Manighetti et al ., , 2009; Scholz , ; Soliva and Benedicto , ; Nicol et al ., ; Martel and Shacat , for normal faults; e.g., Peacock , ; Bürgmann et al ., ; McGrath and Davison , ; Pachell and Evans , ; Farbod et al ., for strike‐slip faults; e.g., Ellis and Dunlap , ; Shaw et al ., ; Davis et al ., for reverse faults] and individual earthquake ruptures [e.g., Scholz and Lawler , ; Manighetti et al ., ; Wesnousky , ; Perrin et al ., ; Cappa et al ., ]. On each fault, the distribution of cumulative displacement along‐strike appears as a fluctuating signal, dominated by large peaks separated by narrower troughs (Figure a).…”
Section: Data Processingmentioning
confidence: 99%
“…[], and Cappa et al . []). Therefore, acquiring more empirical data on natural faults is needed to further constrain the theoretical models.…”
Section: Introductionmentioning
confidence: 99%
“…The model does not account for numerous factors in the faulting process, including opening normal to the fault, nonuniform friction, displacement gradients, influence of fault tips, host rock anisotropy, selfaffine fault geometries, 3-D fault geometries, or pore fluid pressure variability [e.g., Dieterich and Smith, 2009;Griffith et al, 2010;Ritz and Pollard, 2012;Ritz et al, 2015]. As a result, it does not account for changes in elastic moduli in the damage zone resulting from accumulated inelastic deformation [e.g., Faulkner et al, 2006;Cappa et al, 2014;Xu et al, 2014]. However, it does provide a framework with which to investigate the role of friction on off-fault stresses and structural patterns in an elastic medium.…”
Section: Journal Of Geophysical Research: Solid Earthmentioning
confidence: 99%
“…These simple assumptions are supported by observations on natural faults. In particular, while secondary faulting is commonly observed off major fault traces [e.g., Cappa et al , ], in strike‐slip contexts slip partitioning generally occurs between on‐fault lateral and off‐fault vertical slip components [e.g., Armijo et al , ], as observed for the eastern Hope Fault. Since the landforms are laterally offset by a subvertical strike‐slip fault, it is their x‐y planform geometry that most records the lateral offsets [e.g., Ouchi , ].…”
Section: Measurement Of the Fault Lateral Offsetsmentioning
confidence: 99%